Comparison of Methanolic Extract of Piper Betle to Amikacin against the Growth of Pseudomonas aeruginosa - Azalia Ayu Rysaputri; Hery Susilo; Dwi Yuni Nur Hidayati; Irene Ratridewi (Jurnal Kedokteran Brawijaya, 2023)
Pseudomonas aeruginosa is one of the most common pathogens that cause Healthcare-Associated Infections (HAIs). A previous study stated that Piper betle L. extract has antibacterial activity against certain bacteria, including Pseudomonas aeruginosa. This study has the objective of comparing antibacterial activity of the methanolic extract of Piper betle L. and amikacin on the growth of Pseudomonas aeruginosa. This study used the tube dilution method with a sample of Pseudomonas aeruginosa from Microbiology Laboratory Dr. Saiful Anwar General Hospital, Malang. The results of this study showed that the value of MIC and MBC from the methanolic extract of the Piper betle L. treatment was 4800μg/mL. Meanwhile, the amikacin treatment resulted in 0.4μg/mL for MIC and 0.45μg/mL for MBC. From linear regression, it was found that the methanolic extract of Piper betle L. had a β-coefficient value closer to -1 compared to amikacin. Therefore, it can be concluded that the methanolic extract of Piper betle L. has a greater inhibiting effect on the growth of Pseudomonas aeruginosa.